Exploring The Moderation Role of Environmental Leadership Between Environmental Management Accounting and Firm Financial Performance - Gozali, Efva Octavina Donata; Januarti, Indira (Accounting Analysis Journal, 2024)
Purpose: This article examines the relationship between environmental management accounting (EMA), environmental leadership (EL), and firm financial performance in Indonesian corporations. Method: This study uses a Moderated Regression Analysis (MRA) to examine the moderating role of EL. Using secondary data, the research analyses 52 observations from 45 companies listed in the LQ45 Index on the Indonesia Stock Exchange. The unit of analysis is the firm level, with EL measured as the proportion of female commissioners, EMA proxied by the ESG score, and firm financial performance represented by ROA. Control variables include leverage, operating profit, and sales growth to ensure robust results. Findings: The study finds that EMA does have an impact on financial performance, while EL has a negative direction and does not give an impact on strengthening the relationship between EMA and financial performance. The research suggests the importance of implementing EMA practices to enhance company performance. The study also highlights the need for future research to focus on industries closely related to the environment, such as mining companies. Novelty: This study introduces the proportion of female commissioners on the board as a novel proxy for EL within the framework of Indonesian corporations. Unlike prior research focusing solely on EL in generic terms, this approach leverages gender diversity to explore its moderating role between EMA and firm financial performance. By doing so, it provides unique insights into how gender-inclusive leadership can influence environmental practices and corporate outcomes, where female representation on boards is still emerging.